Exploring the sub-eV neutrino mass range with supernova neutrinos (2004)
ABSTRACT: A new method to study the effects of neutrino masses on a supernova neutrino signal is proposed. The method relies exclusively on the analysis of the full statistics of neutrino events, it is independent of astrophysical assumptions, and does not require the observation of any additional phenomenon to trace possible delays in the neutrino arrival times. The sensitivity of the method to the sub-eV neutrino mass range, defined as the capability of disentangling at 95% C.L. the case Mv=1 eV from mv=0, is tested by analyzing a set of synthetic neutrino samples modeled according to the signal that could be detected at SuperKamiokande. For a supernova at the Galactic center success is achieved in more than 50% of the cases. It is argued that a future Galactic supernova yielding several thousands of inverse β decays might provide enough information to explore a neutrino mass range somewhat below 1 eV.